2012
DOI: 10.2298/csis110106043c
|View full text |Cite
|
Sign up to set email alerts
|

Usage of technology enhanced learning tools and organizational change perception

Abstract: This paper presents an analysis of organizational changes perceived by the employees in the organizations where Technology Enhanced Learning was facilitated by tools such as wiki, (we)blog, the Internet forum and the social network, practice often considered as Elearning 2.0. Our research focuses on the technologically advanced organizations, leaders in the CT and IS adoption. We specifically observe the perception of influence on the organizational structure, organizational culture and the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…The development of information and communication technology has drastically changed currency trading. Other studies have found strong relations between the usage of technology-enhanced learning tools and organizational change (Čudanov, Savoiu & Jasko, 2012). For many years, currency trading has been in the domain of banks and financial institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of information and communication technology has drastically changed currency trading. Other studies have found strong relations between the usage of technology-enhanced learning tools and organizational change (Čudanov, Savoiu & Jasko, 2012). For many years, currency trading has been in the domain of banks and financial institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Equally important are the willingness to take risks in implementing blended learning, to work harder when facing difficulties and to provide more motivation for the students. Previous studies have looked at the importance of training in the integration of technology in teaching and learning (Cudanov, Savoiu, & Jasko, 2012;Davies & Sinclair, 2013).…”
Section: Contribution Of the Studymentioning
confidence: 99%
“…In order to ensure the successful cultivate blended learning culture among lecturers in higher education institutions in Malaysia, quality professional development training for educators, senior coaches and technical support staff should be prioritized. It is well documented and highlighted in the relevant literature that the importance of training in integrating technology into the learning process [21][22]. Professional training programs should include information and activities regards to the issue related how to manage the resistance to the changes of pedagogical practices and how to design and integrate lessons in teaching and learning accordingly.…”
Section: Training and Developing Programmentioning
confidence: 99%